SeSy: Enhancing Communication System Reliability through Image-Based Semantic Synchronization - Liu, Xiaoyi; Dong, Chen; Liang, Haotai; Jiang, Hongchao; Xu, Xiaodong; Zhang, Ping (IEEE transactions on communications, 2025)
Semantic communication has emerged as a promising paradigm exhibiting improved robustness compared to traditional approaches under low SNR conditions. Precise synchronization is imperative for accurate semantic communication. However, existing synchronization techniques face challenges reliably achieving synchronization at low SNRs, limiting semantic communication development. To improve synchronization performance, especially under low SNR scenarios, this work proposes an image-based semantic synchronization method (SeSy) leveraging inherent image correlations. SeSy is applicable to both semantic and traditional communication systems. Theoretical analysis establishes bounds on the miss detected ratio (MDR) for SeSy. Experimental results demonstrate that SeSy achieves lower MDR and root mean square error (RMSE) compared to traditional methods across various SNR levels, especially at low SNRs.